A Comprehensive Study on Light Emitting Diode and Analysis of Its Structure (International Journal of Food and Nutritional Sciences, 2022)
The current age of science and technology is one that we are all a part of. Everything is growing more robotic and automated as time passes, and life is now dominated by LEDs (light emitting diodes). Using the Node MCU, we covered making an LED blink in this article. The Server is an open application platform that is used on the ESP8266 and enables the connection of devices and the transmission of messages through Wi-Fi networks. Furthermore, by providing several of the most common application endpoints of embedded devices, such as GPIO (general purpose input/output), PWM (pulse width modulation), and others, it can often meet most of those developers' needs on its own. The term "Internet of things" (IoT) refers to physical objects, some of whom are networked, as well as to processing speed, algorithms, and other approaches. These techniques also interact with things and efficiently move data among computers and applications through the internet. The field has evolved as a result of the convergence of network technologies, including cognitive computing, inexpensive sensors, the more widely used internet of things (IoT), and sophisticated analytics.